Autopsy Across Cultures: Unravelling Beliefs and Ethics - Sharma, Shelu; Sharma, Rituja (Journal of Neonatal Surgery, 2025)
This paper delves into the profound intersection of autopsy practices with the rich tapestry of cultural beliefs, offering a nuanced exploration of the ethical dimensions inherent in diverse societal contexts. Autopsy, an indispensable tool in elucidating the mysteries of mortality, stands at the nexus of medical science and cultural values. However, its practice is deeply imbued with cultural perspectives, shaping attitudes, rituals, and ethical frameworks surrounding post-mortem examinations. Drawing from an array of cultural lenses including Western, Eastern, Indigenous, and religious viewpoints, this study illuminates the intricate mosaic of beliefs that inform autopsy practices globally. Ethical quandaries, such as those pertaining to consent, cultural sensitivity, and the delicate balance between scientific inquiry and cultural reverence, are scrutinized through a comparative lens. Furthermore, through compelling case studies, the paper elucidates how cultural beliefs manifest in autopsy decision-making and the attendant challenges faced by healthcare practitioners. In its conclusion, the paper advocates for the cultivation of culturally sensitive autopsy practices, underscored by a call for heightened cross-cultural understanding to navigate the ethical complexities inherent in the autopsy arena while upholding respect for diverse beliefs and traditions. This study focuses on the cross-cultural concerns related to autopsies, including but not limited to religious and cultural elements, customs, beliefs, and views. The influence of the multicultural approach in forensic pathology on the relatives of the deceased is highlighted by our study. The intercultural phenomena reveal relationships, contradictions, harmonies, and antagonistic relationships that we hope to emphasize.